Before They Were Titans Essays on the Early Works of Dostoevsky and Tolstoy - Allen, Elizabeth Cheresh (Ars Rossica, 2015)
Dostoevsky and Tolstoy are the titans of Russian literature. As mature artists, they led very different lives and wrote vastly different works, but their early lives and writings display provocative kinships, while also indicating the divergent paths the two authors would take en route to literary greatness. The ten new critical essays here, written by leading specialists in nineteenth-century Russian literature, give fresh, sophisticated readings to works from the first decade of the literary life of each Russian author-for Dostoevsky, the 1840s; for Tolstoy, the 1850s. Collectively, these essays yield composite portraits of these two artists as young men finding their literary way. At the same time, they show how the early works merit appreciation for themselves, before their authors were Titans.